2022
DOI: 10.1186/s12894-022-01067-8
|View full text |Cite
|
Sign up to set email alerts
|

A prognosis marker MUC1 correlates with metabolism and drug resistance in bladder cancer: a bioinformatics research

Abstract: Background MUC1 is a type I transmembrane protein that plays an important role in tumor cell signal transduction. Although current studies have shown that MUC1 is upregulated in bladder cancer (BC), the specific mechanism is still unclear. Methods We performed expression analysis, gene set enrichment analysis, survival analysis, immune infiltration analysis, drug sensitivity analysis, and metabolism-related gene expression analysis on TCGA-BLCA, GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Multiple studies have suggested that BC is a highly immunogenic malignant tumor and that the TME is involved in BC progression and prognosis [ 35 , 36 , 37 ]. PD-L1, TMB, and microsatellite instability biomarkers were used to predict the efficacy of treatment [ 38 ]. Therefore, a powerful RBP gene signature should be explored and validated for the prediction of BC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have suggested that BC is a highly immunogenic malignant tumor and that the TME is involved in BC progression and prognosis [ 35 , 36 , 37 ]. PD-L1, TMB, and microsatellite instability biomarkers were used to predict the efficacy of treatment [ 38 ]. Therefore, a powerful RBP gene signature should be explored and validated for the prediction of BC progression.…”
Section: Discussionmentioning
confidence: 99%
“…A number of excellent reviews have been published in recent years that describe the role of mucins in cancer, to cite some of them [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]. Changes in the expression, distribution, and glycosylation of mucins have been well documented in several cancers, providing a rationale for exploring their use as both diagnostic and prognostic markers, as well as targets for the development of cancer therapies.…”
Section: The Role Of Mucin-type O-glycans In Bladder Cancermentioning
confidence: 99%
“…76,77 This protein is upregulated in the breast, 78 colorectal, 79,80 gastric, 81,82 lung, 83 ovarian, 84,85 prostate, 86 pancreatic, 87 and bladder cancers. 77 Ablin. 94 This molecule weighs 33 kDa, and the glycoprotein structure ranges from 0 to 0.4 ng mL À1 .…”
Section: Mucin 1 Proteinmentioning
confidence: 99%
“…There are three distinct regions of the Mucin 1 protein (MUC1) protein: a cytoplasmic domain (containing 69 amino acids), a hydrophobic membrane‐spanning domain (containing 31 amino acids), and an extracellular domain with a sequence of 20‐amino acid repeats 76 . MUC1 has preservation activity and possibly contributes to cell signaling pathways related to cancer progression 76,77 . This protein is upregulated in the breast, 78 colorectal, 79,80 gastric, 81,82 lung, 83 ovarian, 84,85 prostate, 86 pancreatic, 87 and bladder cancers 77 .…”
Section: Qd‐apt Conjugates For Cancer Managementmentioning
confidence: 99%
See 1 more Smart Citation